B
bigbang195
[TEX]\huge \red \fbox{ A_7= \lim_{x \to 0} (\frac{\sqrt[n]{1+ax}-\sqrt[n]{1+bx}}{x})[/TEX]
[TEX]\huge \blue \fbox{A_8 = \lim_{x \to +\infty }(\frac{(x+1)(x^2+1)....(x^n+1)}{\bigg((nx)^n+1 \bigg)^{\frac{n+1}{2}}} [/TEX]
II.Phương pháp 2 . Ta xét bài toán sau :
Bài toán 1 :
Cho a :neq 0 . Chứng minh rằng : [tex]L = \lim\limits_{x\rightarrow 0}\frac{\sqrt[n]{1 + ax} - 1}{x} = \frac{a}{n}[/tex]
Lời giải :
Đặt [tex]y = \sqrt[n]{1 + ax}[/tex] , khi đó từ [tex]x \Rightarrow 0[/tex] , ta có [tex]y \Rightarrow 1[/tex] . Vậy :
[tex]L = \lim\limits_{x\rightarrow 0}\frac{\sqrt[n]{1 + ax} - 1}{x} = \lim\limits_{x\rightarrow 1}\frac{y - 1}{\frac{y^{n} - 1}{a}} = a.\lim\limits_{x\rightarrow 1}\frac{y - 1}{y^{n} - 1} = a. \lim\limits_{x\rightarrow 0}\frac{y - 1}{(y - 1)(y^{n - 1} + . . . + y + 1)} = \frac{a}{n}[/tex] (ĐPCM)
dễ thấy do bậc x ở tử lớn hơn bậc x ở mẫu nên :